Synthesis, insecticidal and fungicidal activities of methyl 2-(methoxyimino)-2-(2-((1-(N′-nitrocarbamimidoyl)-2-hydrocarbylidenehydrazinyl)methyl)phenyl)acetates. Issue 24 (17th February 2016) - Yuan, Xiaoyong; Jia, Changqing; Ma, Yongqiang; Yang, Dongyan; Rui, Changhui; Qin, Zhaohai
Abstract : By combining the sub-structures of strobilurin and guadipyr analogues in one molecule, a series of compounds was designed and synthesized. Some compounds showed excellent insecticidal activity or fungicidal activity. Abstract : N ′-Nitro-2-hydrocarbylidenehydrazinecarboximidamides and methoxyacrylates are two types of important agrochemicals. By combining their key fragments into one framework, a series of the title compounds was designed and synthesized. Some of these compounds have shown excellent insecticidal activities for aphides, for example, the LC50 values of compounds6-06, 6-11 and6-19 against M. perslcae and H. amygdale were found to be 1.9/14.4, 13.4/1.5 and 0.3/38.4 mg L −1 respectively. They were also effective against the mycelium growth of B. cinerea in vitro . Compound6-04 could control (∼100%) cucumber anthrax and rice blast at 100 mg L −1 in vivo, and inhibit the spore germination (∼100%) of vegetable gray mold at 6.25 mg L −1 . These compounds could be considered as potential insecticidal or fungicidal candidates for crop protection. The results of structure–activity relationship (SAR) studies are discussed.